The Effect of Financial Literacy, Personal Income, and Locus of Control in Long-Term Gold Investment Decision - Amanda; Bambang Widagdo; Fika Fitriasari (Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to find out whether there is an influence of financial literacy, personal income, and locus of control on the investment decision of installment gold. This type of research uses quantitative methods with a sample of 97 respondents. Sources of data obtained in this study from distributing questionnaires. While the data analysis technique used in this study uses multiple linear regression analysis. The results of this study indicate that financial literacy has a positive and significant effect on investment decisions in installment gold. Personal income does not affect gold installment investment decisions. Locus of control has a positive and significant effect on gold installment investment decisions. In addition, financial literacy has a dominant influence on investment decisions in gold installments.